The smart relay protection system of traction energy is based on a new criterion. 1. The theory of work - Kostin, M. O.; Mihalichenko, P. Ye. (Science and Transport Progress, 2011)
In the article a new indication of emergency conditions detection for the traction DC power supply system, namely the rate of decreasing the traction substation feeder voltage is suggested. The indication considered allows determining a kind of short circuit. In addition, the circuit design decisions for realization of the protection system based on this indication are proposed.